2020
DOI: 10.3390/sym12081238
|View full text |Cite
|
Sign up to set email alerts
|

Convective Effect on Magnetohydrodynamic (MHD) Stagnation Point Flow of Casson Fluid over a Vertical Exponentially Stretching/Shrinking Surface: Triple Solutions

Abstract: In the current study, the characteristics of heat transfer of a steady, two-dimensional, stagnation point, and magnetohydrodynamic (MHD) flow of shear thickening Casson fluid on an exponentially vertical shrinking/stretching surface are examined in attendance of convective boundary conditions. The impact of the suction parameter is also considered. The system of governing partial differential equations (PDEs) and boundary conditions is converted into ordinary differential equations (ODEs) with the suitable exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…The findings of the boundary layer problem (9-11) demonstrate that multiple branches occur. An analysis of stability is then carried out which has been performed by many researchers [33][34][35][36].…”
Section: Temporal Stability Analysismentioning
confidence: 99%
“…The findings of the boundary layer problem (9-11) demonstrate that multiple branches occur. An analysis of stability is then carried out which has been performed by many researchers [33][34][35][36].…”
Section: Temporal Stability Analysismentioning
confidence: 99%
“…Its applications can be seen in hyperthermia, magnetic cell separation, treatment of some arterial diseases, drug delivery. Lund et al 12 used the similarity variables of transformations to study the steady, two-dimensional, stagnation point and magnetohydrodynamic flow on an exponentially vertical stretching/shrinking surface with convective boundary conditions.They obtained two ranges of solutions in the specific ranges of the physical parameters where three solutions corrospond to the opposing flow. Siddiqui et al 13 presented the numerical solution of magnetohydrodynamic mixed convection within a lid steered square geometry having micropolar fluid.…”
Section: Introductionmentioning
confidence: 99%
“…The flow over a stretching sheet has attracted significant attention in the last few years due to its unique nature and industrial applications. Different studies on stretching sheets can be found in detail in the papers [44][45][46][47][48][49]. Gosh et al [50] used the Tiwari and Das model to investigate the couple stress magnetite-water-based nanofluid motion near a bi-directional stretchable surface incorporating the effects due to non-linear thermal radiations.…”
Section: Introductionmentioning
confidence: 99%